SOME IMPORTANT ISSUES IN THE HISTORY OF KARAKALPAK FOLKLORE AND LITERATURE - Allambergenov, K. (FAN va JAMIYAT, 2021)
The article deals with the characteristics of Karakalpak folklore and literature, their relationship, the role of Karakalpak literature in the history of its emergence and formation. Thus, it is assumed that the question of the involvement of these educators in Karakalpak literature can be properly resolved only by a comparative study of their upbringing in the context of the history of folklore and literature of the Turkic people.